Fine-scale mapping - Balding, David; Morris, Andrew (Henry Stewart Talks, 2004)
Linkage vs. association, The need for fine mapping, The genealogy underlying a sample of case chromosomes, Disease-marker association, Star genealogies and variance adjustment, Coalescent-based approaches, Software: DMLE+ and COLDMAP, Example: CF dataset
Archived at 2021/02/25